(untitled) (Technological Innovations Journal, 2022)
Traditionally, teaching-learning activities in schools in most states of the Mexican Republic had been face-to-face interactions between students and teachers, but obviously in the period of the COVID-SARS-COV-2 pandemic everything changed in the educational context. Because the use of videoconferencing was gaining ground in the academic field, adapting in various ways in the teaching-learning process, such is the case in the field of remote collaborative programming where both social and cognitive skills must be developed. In this work, an empirical study was developed in a non-probabilistic sample of 21 students during a period of 14 weeks at the Polytechnic University of Tulancingo, Hidalgo, Mexico, in order to identify whether personality traits and gender influenced the adoption of distance programming work skills in four factors: negotiation, team functionality, group knowledge building and collaborative programming.